Energy for the future the grand vision - Altekruse, Jorg; Tikhomirov, K. Michael; Gohen, Mitch; Bluett, Rick (Landmark Media Inc., 2000)
The rise in the number and severity of weather phenomena and natural disasters over the past years furnishes ominous proof that the earths climate is changing. Yet at the same time, the global demand for energy is mushrooming - an increase of 300 percent has been predicted for the next fifty years. It is also predicted that fossil fuels the primary cause of the climate changes will have forfeited their status as the leading sources of energy production within a few decades. Earth-shaking visions and endeavors are needed to rethink, redefine and reshape the use of energy and its sources for the future. For inventors and economists both, the race is on to find the most efficient and sustainable exploitation of resources and energy. In addition to the opportunities for cutting costs, the real strength of alternative energy technologies lies in the great diversity of ideas and the flexibility of their application. The choice of an energy source - whether solar, wind, biomass, nuclear or hydroelectric energy is of prime importance. Crucial to the future of both energy systems and the world climate will be how quickly ways to capture and store the energy of the sun can be developed and refined. This is the ultimate source of all forms of commercially viable energy on earth and an inexhaustible one. It was the source of the gift of Prometheus the Titan - he who thinks ahead.